Development of Islamic Education Teaching Materials Based on Applied Behavior Analysis (ABA) and Positive Behavior of Disabled Students - Husnul Khotimah; Ali Murtadho; Abdul Rohman (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2026)
Islamic Religious Education (PAI) is intended to reach every student, including children with intellectual disabilities (tunagrahita). In practice, however, specialized PAI teaching materials for these children are virtually nonexistent. Teachers still rely on textbooks designed for typically developing students or create their own modules without using appropriate methods, directly contradicting National Education Law No. 20 of 2003, Article 5 Paragraph 2, which mandates special education for citizens with physical, emotional, mental, intellectual, or social disabilities. Previous studies on PAI for children with special needs have only described conventional planning and evaluation without developing tailored approaches. This study aims to develop ABA-based PAI teaching materials for children with intellectual disabilities. It employs a literature review method by systematically collecting, reading, recording, and analyzing journals, books, and documents on teaching materials and Applied Behavior Analysis (ABA).The findings demonstrate that ABA-based PAI materials are critically needed. ABA, originally developed for autism, has proven highly effective for other disorders such as ADHD and Asperger’s syndrome, as well as for typically developing children. For tunagrahita students facing significant intellectual and adaptive limitations, this approach systematically shapes specific behaviors into socially acceptable ones and optimally supports PAI competency mastery. In conclusion, ABA-based PAI teaching materials represent a vital innovation that fulfills the national legal mandate for meaningful and inclusive Islamic Religious Education